Service quality and customer satisfaction among students in higher learning institutions of public bus transportation in Kota Kinabalu, Sabah / Lynda Azlina Lim and Vianney Guido - Lim, Lynda Azlina; Guido, Vianney (2016)
SERVQUAL is the quality management framework for the public agencies to the customer by providing a variety of services. The SERVQUAL was first published in 1985, 1988 by Valarie A. Zeithaml, A. Parasuraman & Leonard L. Berry measure quality in the service sector. This study examines a service quality and customer satisfaction among students in higher learning institutions of public bus transportation in Kota Kinabalu. A random sample 150 respondents and all students in higher learning institutions involve with UMS, UiTM and Polytechnic in Kota Kinabalu were distributing the questionnaire. On the student's side, their level of satisfaction, involve in the five dimensions of the SERVQUAL namely tangible, reliability, assurance, empathy and responsiveness. The main finding is all the student use the public bus transportation not associated with the five dimensions of service quality. It also shows that, the service quality attributes that have the factor associated with customer satisfaction in Kota Kinabalu public transport between male and female users was moderate. This means both of the genders are moderate in term of the service quality that provide by the public bus transportation. While investigating the overall customer satisfaction level towards public transportation service in Kota Kinabalu was found that, overall the satisfaction of the student according to the Likert scale was neutral.